2020
DOI: 10.3390/inventions5030026
|View full text |Cite
|
Sign up to set email alerts
|

Open-Source Grinding Machine for Compression Screw Manufacturing

Abstract: Some of the most promising distributed recycling and additive manufacturing (DRAM) technical systems use fused particle fabrication (FPF) or fused granular fabrication (FGF), where compression screws force post-consumer waste plastic through a heated nozzle for direct 3D printing. To assist the technical evolution of these systems, this study provided the details of an invention for a low-cost, easily replicable open-source grinding machine for compression screw manufacturing. The system itself can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…First, the mechanical properties of the prints were weaker than with other methods, due to the non-uniform printing and high porosity that is resulted from the weaker deposition accuracy of a heavy hangprinter head combined with non-uniform feedstock. Future work could develop a new version of the direct waste hangprinter using a smaller recyclebot-based motor and low-cost, opensource custom screws [72] based on recyclebots rather than an FPF/FGF head. Second, the nature of the currently used hangprinter design has a volume and shape limitation, as the larger head can run into the cables.…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…First, the mechanical properties of the prints were weaker than with other methods, due to the non-uniform printing and high porosity that is resulted from the weaker deposition accuracy of a heavy hangprinter head combined with non-uniform feedstock. Future work could develop a new version of the direct waste hangprinter using a smaller recyclebot-based motor and low-cost, opensource custom screws [72] based on recyclebots rather than an FPF/FGF head. Second, the nature of the currently used hangprinter design has a volume and shape limitation, as the larger head can run into the cables.…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…Future study is also needed to improve slicing and other means to overcome the warping observed with large LDPE prints. Lastly, there has been progress on development of custom screws for DRAM, 75 and information from Justino et al , 76 which reported a systematic review of screw-assisted 3D printing equipment, could be used for optimizing additive manufacturing (AM) of LDPE with screw extrusion technology.…”
Section: Resultsmentioning
confidence: 99%
“…First, the mechanical properties of the prints were weaker than with other methods, which is due to non-uniform printing and high porosity that is the result of the weaker deposition accuracy of a heavy hangprinter head combined with non-uniform feedstock. Future work could develop a new version of the direct waste hangprinter using a smaller recyclebot-based motor and low-cost open source custom screws [63] based off of recyclebots rather than an FPF/FGF head. Second, the nature of the currently-used hangprinter design has a volume and shape limitation as the larger head can run into the cables.…”
Section: Discussion and Future Workmentioning
confidence: 99%